Telling the difference between deceiving and truth telling: An experiment in a public space - Eubanks, Dawn L. (2013)
The behavioral experiment presented in this paper investigated deception tasks (both concealment and lying) undertaken in a public space. The degree of risk of deception detection and the demands of self-regulation when deceiving were manipulated. The results showed a significant interaction effect between veracity and risk of deception detection, emerged for the body movement of “hand(s) in pocket(s)”. The incidence of “hand(s) in pocket(s)” was found to increase from truth telling to deceiving conditions when the risk of deception detection was higher, and to decrease from truth telling to deceiving conditions when the risk was lower. Higher risk of deception detection was also found in magnifying the “overall negative and controlled impression” displayed by both deceivers and truth tellers, compared to the lower risk of detection condition. We also discussed the possible effects of risk of deception detection and depletion of self-regulation, on deception behavior. Further studies and the connection between this study and the research community of computer vision and multimodel interaction is also discussed